Dynamics of a headwater system and peatland under current conditions and with climate change. Issue 17 (14th August 2013) - Levison, J.; Larocque, M.; Fournier, V.; Gagné, S.; Pellerin, S.; Ouellet, M.A.
Abstract Interactions between headwater aquifers and peatlands have received limited scientific attention. Hydrological stresses, including those related to climate change, may adversely impact these interactions. In this study, the dynamics of a southern Québec headwater system where a peatland is present is simulated under current conditions and with climate change. The model is calibrated in steady state on field‐measured data and provides satisfactory results for transient‐state conditions. Under current conditions, simulations confirm that the peatland is fed by the fractured bedrock aquifer year‐round and provides continuous baseflow to its outlets. Climate change is simulated through its impact on groundwater recharge. Predicted precipitation and temperature data from a suite of regional climate model scenarios provide a net precipitation variation range from +10% to −30% for the 2041–2070 horizon. Calibrated recharge is modified within this range to perform a sensitivity analysis of the headwater model to recharge variations (+10%, −15% and −30%). Total contribution from the aquifer to rivers and streams varies from +14% to −44% of the baseline for +10% to −30% recharge changes from spring 2010 data, for example. With higher recharge, the peatland receives more groundwater, which could significantly change its vegetation pattern and eventually ecosystem functions. For a −30% recharge, the peatland becomes perched above the aquifer during the summer, fall and winter. Recharge reductions also induce sharp declines in groundwater levels and drying streams. Copyright © 2013 John Wiley & Sons, Ltd.